2010
DOI: 10.1007/s11248-010-9440-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of artificial microRNAs in tomato confers efficient and stable virus resistance in a cell-autonomous manner

Abstract: Expression of artificial microRNAs (amiRNAs) in plants can target and degrade the invading viral RNA, consequently conferring virus resistance. Two amiRNAs, targeting the coding sequence shared by the 2a and 2b genes and the highly conserved 3' untranslated region (UTR) of Cucumber mosaic virus (CMV), respectively, were generated and introduced into the susceptible tomato. The transgenic tomato plants expressing amiRNAs displayed effective resistance to CMV infection and CMV mixed with non-targeted viruses, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(59 citation statements)
references
References 44 publications
0
58
0
1
Order By: Relevance
“…Recent advances like the construction of chimeric IR constructs incorporating sequences derived from different virus species if combined with epidemiological data and pest risk analyses could reduce the effect of mixed virus infections on the resistance (Bucher et al, 2006;Dafny-Yelin & Tzfira, 2007;Kung et al, 2009). Recently, virus resistance was achieved through expression of amiRNAS against viral coding sequences (Ding & Voinnet, 2007;Duan et al, 2008;Niu et al, 2006;Qu et al, 2007;Simon-Mateo & Antonio Garcia, 2006;Zhang et al, 2011). Although there was evidence that amiRNA-mediated virus resistance may not be inhibited by low temperature (Niu et al, 2006) this possibly depends on the plant species examined (Qu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances like the construction of chimeric IR constructs incorporating sequences derived from different virus species if combined with epidemiological data and pest risk analyses could reduce the effect of mixed virus infections on the resistance (Bucher et al, 2006;Dafny-Yelin & Tzfira, 2007;Kung et al, 2009). Recently, virus resistance was achieved through expression of amiRNAS against viral coding sequences (Ding & Voinnet, 2007;Duan et al, 2008;Niu et al, 2006;Qu et al, 2007;Simon-Mateo & Antonio Garcia, 2006;Zhang et al, 2011). Although there was evidence that amiRNA-mediated virus resistance may not be inhibited by low temperature (Niu et al, 2006) this possibly depends on the plant species examined (Qu et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This strategy resulted in a high frequency of produced resistant plants. A most recent approach used modified plant miRNA cistrons to produce a range of antiviral artificial miRNAs (amiRNAs) (Niu et al, 2006;Qu et al, 2007;Schwab et al, 2006;Simon-Mateo & Antonio Garcıa, 2007;Zhang et al, 2011).…”
Section: Strategies For Engineering Resistance To Plant Virusesmentioning
confidence: 99%
“…In plants, amiRNAs have been successfully used for downregulating endogenous genes [25,29,31] and developing transgenic virus resistance against turnip yellow mosaic virus (TYMV), turnip mosaic virus (TuMV) in Arabidopsis [31]; tomato leaf curl virus [34]; cucumber mosaic virus (CMV)in tobacco [35]; CMV in tomato [36] and cassava brown streak virus (CBSV) and Cassava brown streak Uganda virus (CBSUV) in cassava [37].…”
Section: Artificial Mirnas and Virus Resistance In Plantsmentioning
confidence: 99%
“…Indeed several studies demonstrated that artificial miRNAs (amiRNAs) targeting key components of the viral replication machinery can efficiently impair viral growth upon infection [59][60][61][62][63][64][65]. These efforts have revealed that such resistance is cell-autonomous, inheritable, more efficient than siRNA-mediated strategies and successful in blocking viral replication and movement [59,66]. Furthermore transgenic plants expressing dimeric or polycistronic amiRNAs directed against different viruses result in a wider spectrum of viral resistance [60,61,63].…”
Section: Sncrnas and Viruses: New Frontiers Of Defensementioning
confidence: 99%